PENGARUH PENGUNGKAPAN TERHADAP KINERJA DAN RESIKO (STUDI KASUS PADA PERBANKAN SYARIAH DI INDONESIA PERIODE 2006-2012) - Prastika, Nurhikmah Esti (STIE Muhammadiyah Pekalonga, 2013)
InIslamdisclosureis seen asa meanstohelp thesocial and economicjustice(al-Falah) andmeet theobligationsofAllahSWT, the individualandsocietyassociatedwith theorganizationorgroup of peoplein oneeconomicactivity, such asaccountants, managers, owners, governmentandseen asa formof worship. Much research to be done on the relationship between disclosure, risk and performance in the Islamic banking system in this research paper refers to research wan wan hakimah Ibrahim et all (2011). The study was conducted to: Knowing and analyzing the effect of disclosure of risks to the financial statements of Islamic banking in Indonesia, Knowing and analyzing the performance impact on the disclosure of Islamic banking in Indonesia, Knowing and analyze the influence of disclosure on the performance and risks of Islamic banking in Indonesia This study population is all that Islamic banking has been on the Bank Indonesia. While the sample selection is done using the method of purposive sampling in order to obtain a representative sample in accordance with the specified criteria. The criteria of the sample in this study is Islamic Banking (represented by the Islamic Banks) who has reported its financial statements in the year 2006-2011 a total of 11 commercial banks, namely Shariah. Islamic banks which have complete data related to the variables used in the study.The study variable used is Endogenous variables consisting of The disclosure index (DISC), Profitability, Leverage (LEV). The exogenous variables consist of Size, financing,Non Performing Financing (NPF), and investment.